Rapid organic acid mechanochemical extraction of alginate from Laminaria digitata - Kiri Belcher; Franziska Traeger; Sebastian Primpke; Laurie C. Hofmann (Bioresource Technology, 2026)

Effect of submarine hydrothermal activity and emerged landmasses on Paleoarchean Ocean chemistry: Insights from the Tomka iron formation, Daitari Greenstone Belt, Singhbhum Craton, India - Johanna Krayer; Sandra Kienle; Jaganmoy Jodder; Josua J. Pakulla; Carsten Münker; Axel Hofmann; Toni Schulz; Christian Koeberl; Stefan Weyer; Sebastian Viehmann (Chemical Geology, 2026)

Results of the SSM-SICOPS melt tests of the EU-SAFEST project - Gert Langrock; Torsten Keim; Manfred Fischer; Matthias Braun; Sebastian Kohn; Roland Hofmann; Rainer Bezold; Martin Neumeister; Sevostian Bechta; Patrick Isaksson (Annals of Nuclear Energy, 2025)

The last of their kind: Is the genus Scutiger (Anura: Megophryidae) a relict element of the paleo-Transhimalaya biota? - Sylvia Hofmann; Lars Podsiadlowski; Tobias Andermann; Michael Matschiner; Chitra B. Baniya; Spartak N. Litvinchuk; Sebastian Martin; Rafaqat Masroor; Jianhuan Yang; Yuchi Zheng; Daniel Jablonski; Joachim Schmidt (Molecular Phylogenetics and Evolution, 2024)

Unlocking the potential: unveiling tyrphostins with Michael-reactive cyanoacrylate motif as promising inhibitors of human 5-lipoxygenase - Maximilian Molitor; Amelie Menge; Sebastian Mandel; Sven George; Susanne Müller; Stefan Knapp; Bettina Hofmann; Dieter Steinhilber; Ann-Kathrin Häfner (Pflügers Archiv - European Journal of Physiology, 2024)
Human 5-lipoxygenase (5-LO) is the key enzyme in the biosynthesis of leukotrienes, mediators of the innate immune system that also play an important role in inflammatory diseases and cancer. In this study, we present compounds, containing a Michael-reactive cyanoacrylate moiety as potent inhibitors of 5-LO. Representatives of the tyrosine kinase inhibitor family called tyrphostins, structurally related to known 5-LO inhibitors, were screened for their 5-LO inhibitory properties using recombinant human 5-LO, intact human PMNL (polymorphonuclear leukocytes), and PMNL homogenates. Their mode of action was characterized by the addition of glutathione, using a fourfold cysteine 5-LO mutant and mass spectrometry analysis. SAR studies revealed several members of the tyrphostin family containing a Michael-reactive cyanoacrylate to efficiently inhibit 5-LO. We identified degrasyn (IC 50 0.11 µM), tyrphostin A9 (IC 50 0.8 µM), AG879 (IC 50 78 nM), and AG556 (IC 50 64 nM) as potent 5-LO inhibitors. Mass spectrometry analysis revealed that degrasyn and AG556 covalently bound to up to four cysteines, including C416 and/or C418 which surround the substrate entry site. Furthermore, the 5-LO inhibitory effect of degrasyn was remarkably impaired by the addition of glutathione or by the mutation of cysteines to serines at the surface of 5-LO. We successfully identified several tyrphostins as potent inhibitors of human 5-LO. Degrasyn and AG556 were able to covalently bind to 5-LO via their cyanoacrylate moiety. This provides a promising mechanism for targeting 5-LO by Michael acceptors, leading to new therapeutic opportunities in the field of inflammation and cancer.

Exploring Paleogene Tibet's warm temperate environments through target enrichment and phylogenetic niche modelling of Himalayan spiny frogs (Paini, Dicroglossidae) - Sylvia Hofmann; Dennis Rödder; Tobias Andermann; Michael Matschiner; Jendrian Riedel; Chitra B. Baniya; Morris Flecks; Jianhuan Yang; Ke Jiang; Jiang Jianping; Spartak N. Litvinchuk; Sebastian Martin; et al. (Molecular Ecology, 2024)
The Cenozoic topographic development of the Himalaya‐Tibet orogen (HTO) substantially affected the paleoenvironment and biodiversity patterns of High Asia. However, concepts on the evolution and paleoenvironmental history of the HTO differ massively in timing, elevational increase and sequence of surface uplift of the different elements of the orogen. Using target enrichment of a large set of transcriptome‐derived markers, ancestral range estimation and paleoclimatic niche modelling, we assess a recently proposed concept of a warm temperate paleo‐Tibet in Asian spiny frogs of the tribe Paini and reconstruct their historical biogeography. That concept was previously developed in invertebrates. Because of their early evolutionary origin, low dispersal capacity, high degree of local endemism, and strict dependence on temperature and humidity, the cladogenesis of spiny frogs may echo the evolution of the HTO paleoenvironment. We show that diversification of main lineages occurred during the early to Mid‐Miocene, while the evolution of alpine taxa started during the late Miocene/early Pliocene. Our distribution and niche modelling results indicate range shifts and niche stability that may explain the modern disjunct distributions of spiny frogs. They probably maintained their (sub)tropical or (warm)temperate preferences and moved out of the ancestral paleo‐Tibetan area into the Himalaya as the climate shifted, as opposed to adapting in situ. Based on ancestral range estimation, we assume the existence of low‐elevation, climatically suitable corridors across paleo‐Tibet during the Miocene along the Kunlun, Qiangtang and/or Gangdese Shan. Our results contribute to a deeper understanding of the mechanisms and processes of faunal evolution in the HTO.

Stromatolitic carbonates from the Middle Miocene of the western Pannonian Basin reflect trace metal availability in microbial habitats during the Badenian Salinity Crisis - Sebastian Viehmann; Robert Kujawa; Simon V. Hohl; Nathalie Tepe; Alexandra S. Rodler; Thilo Hofmann; Erich Draganits (Chemical Geology, 2023)

Experimental Characterisation and Field Experience of a Reusable, Modified Polyurethane Foam for the Mechanical Clean-Up of Oil Spills on the Sea Surface - Daniel Niehaus; Sebastian Hofmann; Srividya Bairamangala Kumar; Marko Hoffmann; Jesús Cisneros-Aguirre; Michael Schlüter (Journal of Marine Science and Engineering, 2022)
Oil spills at sea, such as the Deepwater Horizon incident in 2010, are devastating environmental hazards, especially for biodiversity in the maritime ecosystem. In order to help the restoration of coastlines, it is critical to clean the oil up quickly and efficiently with various measures, such as the use of barriers, skimmers, sorbents, dispersing agents, in situ burning, and biological agents. However, most of them still cause high remediation costs; are inefficient, non-reusable, and not environmentally friendly; lack a convenient desorption method; or are simply not yet ready to use in a real-case scenario, where high amounts of hydrocarbons must be removed. Therefore, in this work, a reusable modified polyurethane foam for oil absorption on the sea surface is presented and characterised. Due to a chemical formulation with a special co-polymer, its oleophilic properties are strongly enhanced. Laboratory soaking tests with different oils and a mixture of Louisiana sweet crude oil with artificial sea water (ASW) are conducted. To do so, a pneumatic press with adjustable pressures was used to characterise the foam’s capability to recover oil between 10 and 18 times its own weight for a period of up to 50 consecutive repetitions with a maximum saturation in less than one minute. Sequential trials with different oil mass fractions in ASW determined a decreasing content of recovered ASW with increasing amounts of crude oil, while, in all cases, the total oil recovery rate proved to be more than 90% within one’s standard deviation. Finally, practical applications of sorption methods are presented to give an idea of difficulties encountered in real remediation scenarios.

Styrene-acrylonitrile-copolymer and acrylonitrile-butadiene-styrene-copolymer: a study on extractable and migratable oligomers - Marie Kubicova; Elise Puchta; Sebastian Säger; Constanze Hug; Sandra Hofmann; Thomas J. Simat (Food Additives & Contaminants: Part A, 2022)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Where does the river end? Drivers of spatiotemporal variability in CO 2 concentration and flux in the inflow area of a large boreal lake - Hannah E. Chmiel; Hilmar Hofmann; Sebastian Sobek; Tatyana Efremova; Natacha Pasche (Limnology and Oceanography, 2020)
River inflow affects the spatiotemporal variability of carbon dioxide (CO 2 ) in the water column of lakes and may locally influence CO 2 gas exchange with the atmosphere. However, spatiotemporal CO 2 variability at river inflow sites is often unknown leaving estimates of lake‐wide CO 2 emission uncertain. Here, we investigated the CO 2 concentration and flux variability along a river‐impacted bay and remote sampling locations of Lake Onego. During 3 years, we resolved spatial CO 2 gradients between river inflow and central lake and recorded the temporal course of CO 2 in the bay from the ice‐covered period to early summer. We found that the river had a major influence on the spatial CO 2 variability during ice‐covered periods and contributed ~ 35% to the total amount of CO 2 in the bay. The bay was a source of CO 2 to the atmosphere at ice‐melt each year emitting 2–15 times the amount as an equally sized area in the central lake. However, there was large interannual variability in the spring CO 2 emission from the bay related to differences in discharge and climate that affected the hydrodynamic development of the lake during spring. In early summer, the spatial CO 2 variability was unrelated to the river signal but correlated negatively with dissolved oxygen concentrations instead indicating a stronger biological control on CO 2 . Our study reveals a large variability of CO 2 and its drivers at river inflow sites at the seasonal and at the interannual time scale. Understanding these dynamics is essential for predicting lake‐wide CO 2 fluxes more accurately under a warming climate.

Mibefradil represents a new class of benzimidazole TRPM7 channel agonists - Sebastian Schäfer; Silvia Ferioli; Thomas Hofmann; Susanna Zierler; Thomas Gudermann; Vladimir Chubanov (Pflügers Archiv - European Journal of Physiology, 2016)

RNAi in murine hepatocytes: the agony of choice—a study of the influence of lipid-based transfection reagents on hepatocyte metabolism - Jan Böttger; Katrin Arnold; Carlo Thiel; Christiane Rennert; Susanne Aleithe; Ute Hofmann; Sebastian Vlaic; Susanne Sales; Andrej Shevchenko; Madlen Matz-Soja (Archives of Toxicology, 2015)